Icons for Health Effects of Cigarette Smoke: A Test of Semiotic Type - Lazard, Allison J. (J Behav Med, 2017)
PURPOSE: We sought to identify icons to effectively communicate health harms of chemicals in cigarette smoke. METHODS: Participants were a convenience sample of 701 U.S. adults. A within-subjects online experiment explored the effects of icon semiotic type: symbolic (arbitrary, most abstract), indexical, and iconic (representative, most concrete). Outcomes were perceived representation, affect toward smoking, elaboration, perceived severity, and perceived effectiveness. RESULTS: For not-easy-to-visualize harms of cancer and addiction, symbolic icons received the highest ratings (all p<.001). For easy-to-visualize symptoms of heart attack/stroke, indexical icons received the highest ratings (all p<.001). For easy-to-visualize harm of reproductive organ damage, the iconic image did best (all p<.001). Icon type often had a larger impact among participants with higher health literacy. CONCLUSIONS: Symbolic icons may be most effective for health effects not easily visualized. Iconic or indexical icons may be more effective for health effects attributable to specific body parts or symptoms.